2023
DOI: 10.1242/jeb.245316
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress and restricted diet reduce bill-mediated heat dissipation in the song sparrow (Melospiza melodia): implications for optimal thermoregulation

Abstract: We used thermal imaging to show that two environmental factors—acute stress and diet—influence thermoregulatory performance of a known thermal window, the avian bill. The bill plays important roles in thermoregulation and water balance. Given that heat loss through the bill is adjustable through vasoconstriction and vasodilation, and acute stress can cause vasoconstriction in peripheral body surfaces, we hypothesized that stress may influence the bill's role as a thermal window. We further hypothesized that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We used maximum Teye as recommended by Jerem et al (2015Jerem et al ( & 2019 as well as recorded in recent studies (e.g. Robertson et al 2020a;Zuluaga & Danner 2023, and the minimum Tbeak to gain insight on the maximum state of vasoconstriction for this body surface (Tattersall et al, 2009). Finally, we estimated egg surface temperature (Tegg) as the mean of average length and width surface temperature.…”
Section: Thermal Image Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We used maximum Teye as recommended by Jerem et al (2015Jerem et al ( & 2019 as well as recorded in recent studies (e.g. Robertson et al 2020a;Zuluaga & Danner 2023, and the minimum Tbeak to gain insight on the maximum state of vasoconstriction for this body surface (Tattersall et al, 2009). Finally, we estimated egg surface temperature (Tegg) as the mean of average length and width surface temperature.…”
Section: Thermal Image Collection and Analysismentioning
confidence: 99%
“…Those contrasted findings might be explained by at least three factors: 1. variation in body size, since smaller individuals/species are expected to favour internal heat conservation by reducing more markedly peripheral blood flow and surface temperature compared to large ones (thermoprotective hypothesis; Robertson et al, 2020a); 2. differences in the thermal environment, since it has been shown that during acute stress response, heat conservation is favoured below the thermoneutral zone while heat dissipation is favoured above its upper limit (Robertson et al, 2020a); 3. the various delays at which Teye was measured in response to acute stress, since for instance the increase in Teye found by Ikkatai and Watanabe (2015) was short-lived (visible 5 min after the stressor, but not later on during the 30 min measurement period). It is important to note that Teye and Tbeak can show very rapid and nonlinear changes in response to acute stress, that are likely to be missed by most studies not using continuous thermal image recording (Jerem et al, 2019;Jerem and Romero, 2023;Zuluaga and Danner, 2023). For instance, Zuluaga et al (2023) found an initial drop in Tbeak following exposure to stressor, with a recovery to baseline levels after only 2 minutes, while Jerem et al 2019 found an initial drop in Teye lasting less than 15s, followed by an increase above baseline from 15 to 75 seconds.…”
Section: Stress-induced Changes In Surface Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation